Comportamento espacial da cultura canavieira no Estado de Sao Paulo, em 1975. - Dos Santos, M. J.Z. (My University, 1984)
To demonstrate the spatial behavior of the sugar cane crop in the state of Sao Paulo, we have drawn cartogrames which refer to the area cultivated with sugar-cane in the municpal unities. Presents the distribution and concentration of the crop in 1975, based on government sources.-English summary
(Spatial behaviour of the sugar cane crop in Sao Paulo state in 1975).